Pediatric Pseudo papillary Pancreatic Tumor: A Case Based Review - Mir Ibrahim Sajid; Ayesha Saleem; Muhammad Arshad (Journal of the Pakistan Medical Association, 2021)
Introduction The solid pseudo papillary neoplasm (SPN) of the pancreas also known as a papillary-cystic tumor or Frantz tumor, is a distinct epithelial neoplasm of unfamiliar origin. Solid pseudo papillary neoplasm of the pancreas is a low-grade malignant tumor derived from exocrine cells and composed of poorly cohesive epithelial cells, forming solid and pseudo papillary arrangement and lacking a specific line of pancreatic epithelial differentiation [1]. In adult population it accounts for approximately 2% to 3% of pancreatic neoplasms but differs from other pancreatic tumors by a female predominance and a low risk of malignancy. SPN for the most part occurs in the younger population and occasionally in children, contrary to other pancreatic carcinomas. It also seems to have a predilection for Asian and African American women [2]. Continuous...